ANALISIS POTENSI DAN DAMPAK KEBOCORAN GAS HIDROGEN PADA HYDROGEN PLANT DI INDUSTRI PELUMAS - Setiawan, Adhi; Hanifah, Dian Nur; Nugroho, Agung; Dermawan, Denny (2477 - 6165, 2017)
The increasing need of industrial pure hydrogen is growing. One of its roles is petroleum industry purification. High purity hydrogen (99.99%) was obtained from methane using Steam Methane Reforming Method in hydrogen plant unit. Hydrogen is a very dangerous chemical element with its flammable characteristic. This research was conducted especially on purification system. Quantitative analysis was used to determine hydrogen leakage frequency, consequence modeling, and risk estimation that would be risen. The analysis results showed that the highest frequency occured in unignited release events. Jet fire scenario produced the longest fire length in HPU for about 27 meters. Jet fire scenario impact produced the farthest secure distance in case of a leakage in HPU section of 60 meters. Flash fire produced the farthest distance loss in a leakage case in HPU of 80 meters, and explosion at 200 meters radius would will have a blast overpressure 7.62 psig with 22% fatality estimation of the population. Keywords: Hydrogen Purification Unit, Hydrogen, Consequence Modeling, Risk.